Performance Evaluation of Ciphers Using CRYPTOOL 2.0 (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Cryptography is an emerging technology, which is important for network security. Research on cryptography is still in its developing stages and considerable research effort is required. This paper includes the complete step by step implementation of advance encryption technique, i.e. encrypting and decrypting 128 bit data using the AES and its modification for enhanced reliability and security. The encryption process consists of the combination of various classical techniques such as substitution, rearrangement and transformation encoding technique. The encryption and decryption module include the key expansion module which generates the key for all iterations. The modification includes the addition of an arithmetic operation and a route transposition cipher in the attacks iterative rounds. The key expansion module is extended to double the number of iterative rounds in order to increase its immunity against unauthorized attacks.